Talk & Tour Record to Archive: IMD313 Academic visit to State Record Repository Pustaka Negeri Sarawak / Suhaida Halamy - Halamy, Suhaida (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
In education, we believe in embracing various approaches to teaching and learning beyond the confines of the classroom. By incorporating site visits, hands-on experiences, and thorough research, we can ignite curiosity and bolster students' understanding and proficiency in their subjects. For instance, the course IMD313 Foundation of Archives takes a proactive step by organizing academic visits, providing students with a firsthand encounter with the actual records and archives management. This enriching opportunity is available to all Semester 5 students of the Diploma of Management Information, allowing them to delve deeper into the world of archives and records.